Commemoration of the Mawlid and the Sekaten Tradition at the Yogyakarta Palace - Putriditya, Alya Ramadhani; Soekarba, Siti Rohmah; Widodo, Widodo (Abjad Journal of Humanities & Education, 2024)
This article explores the Sekaten Tradition at the Yogyakarta Palace as a commemoration of Mawlid. The tradition has been alive and well in society since the Demak Kingdom. Initially,  Islamic religious leaders used traditional and religious acculturation to attract people to gather as well as a means of preaching. In its development, the sekaten ceremony became a form of Javanese cultural identity commemorating Islamic religious holidays. In Indonesia, the sekaten tradition is a tradition that lives and develops in society. Sekaten is no longer a tribal identity, but over time, it has become a tradition carried out by some people and a marker of respect for the Islamic holiday, namely the birth of the Prophet. The shift in function from preaching media to the realm of ceremonies occurs not only in the sekaten tradition but also in other traditions. Through a cultural approach, this research shows how Sekaten is a means of expressing the traditions of Yogyakarta society. By analyzing its history, meaning and function today, Sekaten can live across the ages with dynamic forms and changes in function. This research shows that the sekaten tradition can provide a line of cultural order that is followed and adhered to by the community in the eco-bio-cultural realm. The resilience of Javanese culture, which is acculturated to the religion of the people who own it, can become a means to exist in various domains of life beyond time. This research expresses today's sekaten tradition as a means of existence for rulers and society through culture. Javanese traditions instituted by the palace as a source and patron of culture will become icons and cultural forces. The Sekaten tradition is one of the sacred traditions in Yogyakarta. This tradition was created as a form of respect for the Prophet Muhammad.